Percutaneous coronary interventions for ST elevation myocardial infarction in different age groups - I. S. Bessonov; V. A. Kuznetsov; E. A. Gorbatenko; S. S. Sapozhnikov; I. P. Zyryanov (Сибирский научный медицинский журнал, 2021)
Given the global trend of population aging, it is natural to see an increase in the number of percutaneous coronary interventions (PCI) performed in patients of older age groups.The aim of this study was to compare the results of percutaneous coronary interventions (PCI) in different age groups and find a predictors of hospital mortality. Methods. Data were collected from 1649 patients with STEMI who were admitted to the coronary care unit and underwent PCIs from2006 to 2017. Patients were divided into 3 age groups according to World Heals Organization classification. The first group consisted of 850 patients aged from 18 to 59 years, the second group consisted 620 patients aged from 60 to 74 years, and third group consisted of 179 patients aged from 75 years and older. Results. The rate of in-hospital death was statistically significant lower in younger groups (groups 1-2: 2.2 % vs 5.8 %, р<0.001; groups 1-3: 2.2 % vs 16.2 %, р<0.001; 2-3: 5.8 % vs 16.2 %, р<0.001). After multivariate adjustment the independent predictor of death were age (odds ratio (OR) =1.08; 95 % confidence interval (CI) 1.05-1.11, р<0.001), anterior myocardial infarction (OR=2.03; 95 % CI 1.15-3.59, р=0.015), Syntax score (OR=1.05; 95 % CI 1.02-1.09, р=0.001), ventricular arrhythmias (OR=4.98; 95 % CI 2.49-9.96, р<0.001), blood glucose level at admission (OR=1.06; 95 % CI 1.01-1.13, р=0.040), PCI failure (OR=5.05; 95 % CI 2.47-10.3, р<0.001), Killip class III-IV (OR=6.01; 95 % CI 3.12–11.6, р<0.001), total ischemia t-me >180 minutes (OR=4.39; 95 % CI 1.78-10.8, р=0.001). Conclusions. PCIs for STEMI in older age groups were associated with worse in-hospital outcomes. Age, anterior myocardial infarction, Syntax score, ventricular arrhythmias, blood glucose level at admission, PCI failure, Killip class III-IV, total ischemia time >180 minutes were the independent predictor of death.